PEMBERDAYAAN PKK MELALUI KEGIATAN EKONOMI PRODUKTIF - Annisa Fatimah (P3M Politeknik Negeri Malang, 2023)
This activity provide a knowledge sharing related to simple entrepreneurship education and training to the PKK team so that they can become an agents of change for housewives in Urek - Urek, Asrikaton Village - Malang. As is well knhe development of the home industry in Indonesia is absolutely needed during this pandemic. Housewives have a savior potential for their family economic. Therefore, the one way to empowerment the housewives is through various PKK activities, which is have an objective to improve a welfare of its members with various trainings. The initial step for empowering housewives as contributors to strengthening the community's economy is to provide information, knowledge and skills, which must be carried out in multi aspects, they are community, social, cultural aspects, government policies and marketing potential for them. Entrepreneurial ideas, planning strategies, and marketing continues to evolve into the needs of today's society. The PKM activity program is planned to be carried out in April 2022. This time selection has been coordinated with the PKK Team as a host for this by inviting all parties related to the PKM program. The presence of lecturers and students who are also entrepreneurial practitioners is expected to provide enlightenment and new knowledge that is quite meaningful for all participants.